Towards Trasparent Data Access with Context Awareness - Wrzeszcz, Michał; Kitowski, Jacek; Słota, Renata (Computer Science, 2018)
Applying the principles of open research data is an important factor accelerating the production, analysis of scientific results and worldwide collaboration. However, still very little data is being shared. The aim of this article is analysis of existing data access solutions in order to identify reasons for such situation. After analysis of existing solutions and data access stakeholders needs, the authors propose own vision of data access model evolution.